Disclosing the hertzian space. (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2019)
We are currently facing a reality that is influenced by wireless communications, networks, data flows, configuring a new hertzian space where people coexist in a permanent state of connection. The research will focus, precisely in said invisible space, as a place of exploration and artistic intention, presenting the processes and practices that make it perceptible.
Keywords: Wireless communication; hertzian space; Inmaterial creation; Data aesthetics; Reveal; Informational city